Genome-wide identification and expression profiling of bHLH transcription factors associated with ferulic acid biosynthesis in Angelica sinensis - Arshad, Khadija Tehseen; Li, Chaohui; Li, Lesong; Wang, Juan; Chen, Junwen; Zhao, Yan (Frontiers in Plant Science, 2025)
This study identifies 148 bHLH transcription factors in Angelica sinensis and reveals four putative candidates associated with ferulic acid biosynthesis, providing a genetic foundation for metabolic engineering to enhance the plant’s medicinal value. The basic helix-loop-helix (bHLH) proteins regulate plant growth, development, stress responses, and secondary metabolites. While well-characterized in woody plants, they remain unexplored in Angelica sinensis (A. sinensis), a medicinal plant renowned for bioactive compounds including ferulic acid. Therefore, we systematically identified and characterized bHLH transcription factors in A. sinensis through whole-genome analysis and transcriptome profiling, identifying putative genes potentially regulating ferulic acid biosynthesis. Bioinformatic analyses were employed to characterize the physicochemical properties, gene structures, conserved motifs/domains, phylogenetic relationships, chromosome localization, collinearity, cis-acting elements, and transcriptome expression patterns of AsbHLHs. A total of 148 AsbHLH genes were annotated from the genomic database of A. sinensis, classified into 16 subfamilies based on the phylogenetic analysis. Results revealed that these transcription factors encode hydrophilic proteins (83–741 aa; 9.6–80.8 kDa), with nearly all localized to the nucleus. Gene structure analysis showed exon numbers ranging from 1 to 18, while MEME motif analysis identified five conserved motifs (1–5) shared across most AsbHLH proteins. Promoter analysis uncovered abundant cis-elements associated with growth, secondary metabolism (including ferulic acid biosynthesis), and stress responses. WGCNA revealed turquoise module contained 40 bHLH and five phenylpropanoid pathway-specific genes, from which PPI and phylogenetic analyses pinpointed four putative genes potentially associated with ferulic acid production. Quantitative RT-PCR validated these candidates, showing expression patterns consistent with transcriptome data. This study provides the first comprehensive genomic/transcriptomic resource for AsbHLH genes in A. sinensis, highlighting their secondary metabolic roles. Identified candidates enable genetic engineering strategies to boost ferulic acid production, enhancing A. sinensis’ medicinal value.